2005
DOI: 10.4141/p04-139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fall and spring seeding on canola productivity in the Peace River region of northern Alberta

Abstract: . 2005. Effect of fall and spring seeding on canola productivity in the Peace River region of northern Alberta. Can. J. Plant Sci. 85: 641-644. The feasibility of dormant seeding canola in the fall in the Peace River region of northern Alberta was assessed. Results indicated that there is a significant risk of crop failure with fall seeding, mainly due to poor spring seedling emergence. Where a fall-seeded canola crop established, flowering and seed maturity occurred earlier even though plant densities were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A study at Scott, Saskatchewan found that yields of late fall-planted canola were similar to those of early spring-planted canola (Kirkland and Johnson 2000). However, subsequent studies across multiple sites concluded that early spring-planted canola reduced risk and optimized yield and quality compared with fall-planted canola (Karamanos et al 2002;Clayton et al 2004a;Johnson et al 2004b;O'Donovan et al 2005). Fall planting of canola peaked in 1999 at about 40 000 ha and by 2005 was less than 1000 ha (E. Johnson, personal communication 2005).…”
Section: Herbicide-resistant Crop Productivitymentioning
confidence: 99%
“…A study at Scott, Saskatchewan found that yields of late fall-planted canola were similar to those of early spring-planted canola (Kirkland and Johnson 2000). However, subsequent studies across multiple sites concluded that early spring-planted canola reduced risk and optimized yield and quality compared with fall-planted canola (Karamanos et al 2002;Clayton et al 2004a;Johnson et al 2004b;O'Donovan et al 2005). Fall planting of canola peaked in 1999 at about 40 000 ha and by 2005 was less than 1000 ha (E. Johnson, personal communication 2005).…”
Section: Herbicide-resistant Crop Productivitymentioning
confidence: 99%
“…Results have varied for different ecozones, with more positive results for late fall seedings in areas that have more stable fall and winter temperatures, and a consistent insulating snow cover (Johnson et al 2004). Poor seedling emergence in the spring may also result in low yields for late fall seedings, perhaps due to low temperatures and drying of soil following spring germination, or insect feeding (O'Donovan et al 2005) The success of dormant seeding is dependent on freeze-up and snow cover soon after seeding, with the snow maintained throughout the winter. Dormant seedings are usually delayed until the soil is cool and germination will not occur in the fall, usually late October to early November, when seeding conditions are often poor in the Great Plains region of western Canada.…”
mentioning
confidence: 99%